La lectura crítica en el desarrollo del aprendizaje en los estudiantes de sexto año de Educación Básica de la Unidad Educativa “José Joaquín Olmedo. - Guano Rivera, Andrea Elizabeth (2020)
The proposed educational intervention project is established as a pedagogical strategy for teachers, thus applying methods or techniques that generate significant learning in students and solving different problems in their acquisition, for this reason the project is proposed with the topic THE CRITICAL READING IN THE DEVELOPMENT OF LEARNING IN STUDENTS OF SIXTH YEAR OF BASIC EDUCATION, OF THE EDUCATIONAL UNIT “JOSÉ JOAQUÍN OLMEDO, presenting a possible solution through a proposal that is based on innovative and interactive activities between the teacher and The student, in addition to being participatory, creative and playful, with the purpose of improving the language skills, abilities and skills that are exposed through reading, which will be an important contribution in the acquisition of new knowledge and give a judgment of value in what has been learned. The approach of this research project, arises from the problems that students have in the reading process, they maintain a scanned reading, without establishing any type of argument, contextualization or analysis of what has been read; aspects evidenced in the students of sixth year of basic education, attributing these inconveniences to the ignorance of the teachers in applying innovative strategies in relation to the critical reading, maintaining the traditionalism and monotony in the reading process, harming their linguistic abilities, and allowing the student that of a critical value to the reading presented. In the execution of the research, a direct observation was made in the first instance on the various problems and effects that students in the sixth year of basic education have in relation to critical reading in the development of learning, in addition to identifying the strategy used by students. teachers according to the needs identified, for this reason a proposal based on the design, planning, execution and evaluation of activities that improve the student's reading skills is exposed. In this way, significant learning can be achieved in students.